Definition, reasons, and risk factors for mortality of patients listed for liver transplantation – a single-center study - Peschel, Georg; Kraft, Ina-Christine; Ilkhtchoui, Ramin; Schmid, Stephan; Sinner, Barbara; Scherer, Marcus N; Mueller-Schilling, Martina; Weigand, Kilian (Zeitschrift für Gastroenterologie, 2020)
Background In Germany, following the principle “sickest first”, patients awaiting liver transplantation (LTPL) are often transplanted with high MELD score and run the risk that they can no longer be transplanted, getting “too sick for transplant”.Methods In a retrospective single-center study, we analyzed the mortality of adult patients on the waiting list for LTPL during the years 2014 to 2017. To stratify risk factors, we compared characteristics of deceased and transplanted patients.Results The main reasons for mortality were sepsis (42.9 %), malignancy (24.3 %) and bleeding (10.0 %). Risk factors for mortality (OR, univariate logistic regression, p < 0.05) were acute on chronic liver failure (ACLF), loss of E-MELD, sepsis, pneumonia, proof of pathogens, candidemia, stay at ICU, multiple organ failure and mechanical ventilation. Multivariate analysis revealed pneumonia (p < 0.001) and high MELD (p = 0.031) as risk factors. Transplantation was more likely in patients with E-MELD. We suggest a Waiting List Mortality Index for Transplantation (WMIT), by dividing deceased patients to transplanted patients to assess mortality. Average WMIT in our cohort was 0.65.Conclusions Mortality on the waiting list is mainly determined by pneumonia and infections in high-MELD patients. Therefore, patients with ACLF after infections should be prioritized for LTPL. A WMIT might suitably represent waiting list mortality.
Keywords: liver transplantation; waiting list; infection; mortality; pneumonia; ACLF; MELD